(untitled) (Indian Journal of Animal Production and Management, 2025)
The present study was conducted to investigate the effect of supplementation of mannan-oligosaccharide (MOS) on biochemical profile in SVVU T17 crossbred pigs. Twenty-four SVVU T17 crossbred male grower pigs above 2 months of age were randomly divided into four groups with six piglets in each group i.e., T0, T1, T2 and T3 groups. The experiment was conducted for 45 days and at the end of experiment blood samples were collected for estimation of biochemical profile. There was a significant decrease (P<0.05) in alanine transaminase (ALT) and aspartate amino transferase (AST) levels in T2 and T3 groups compared to control T0 group. There was a significant decrease (P<0.05) in creatinine levels in T3 groups compared to control group. Amylase levels were significantly increased (p<0.05) in T2 and T3 groups compared to T1 and control groups. Whereas, bicarbonate levels were significantly lowered in T2 and T3 groups compared to T1 and T0 groups. The calcium levels were significantly lower in T2 and T3 groups compared to T0 and T1 groups. Phosphorus showed a significant decrease (P<0.05) in all the MOS supplemented groups compared to control group. Higher chloride values were seen in T2 and T3 groups compared to T0 and T1 groups. BUN, ALP, bilirubin, sodium and potassium did not differ significantly (p>0.05) among treatment groups when compared with control group. In conclusion, mannan-oligosaccharide had a positive influence on biochemical parameters of SVVU T17 crossbred pig.